From national to regional narratives - Miklošević, Željka (2011)
Unlike the conventional museum practices of collecting, research and communicating of segmented cultural reality in isolating conditions (building), the authors of the paper propose the concept of a national museum which derives from the theoretical and practical standpoint of ecomuseology, that is, the concept of a national eco-museum, in its physical and virtual form. Taking into account a great cultural and geographical diversity of Croatia, which is its important characteristic, this museum could represent Croatians if organized according to a model which fosters regional characteristics – one that stays within the state boundaries but that is conceptually decentralized. Empowerment of regionalism could furthermore enable cross-border cooperation between communities which are much more similar culturally and geographically than individual cultural entities within Croatia or any other nation state. Such a development projected in the future might lead to the formation throughout Europe of numerous museums of regions which could more genuinely create sense of place through regional narratives, and thereby replace the domination the national museums have had for such a long time.